JUDGE CONSIDERATIONS IN ACCEPTING UNDERAGE MARRIAGE APPLICATIONS IN LUWUK RELIGIOUS COURT - N. A. Sustiono; Marzuki Marzuki; Sidik Sidik (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
This paper aims to explore the judge consideration to accept underage marriage aplication in Luwuk Religious Court. This reseach was qualitative approach. The result showed that Judges' considerations in giving marriage dispensation decisions to minors have several impacts, namely positive impacts which can avoid promiscuity, prevent a relationship, and learn to be responsible. The negative impact of dropping out of school, psychological and health impacts. In the Maslahah Perspective on Judges' Considerations in Giving Underage Marriage Dispensaation Decisions regarding the determination by judges in cases, it is in accordance with maslahah, especially in the context of maintaining, because it can avoid promiscuity and can realize legal goals, especially in the context of maintaining offspring.